1990
DOI: 10.1136/gut.31.7.791
|View full text |Cite
|
Sign up to set email alerts
|

Histamine release from gut mast cells from patients with inflammatory bowel diseases.

Abstract: Inflammatory mediators from intestinal mast cells may serve as initiators of acute and delayed inflammation. Mast cell histamine release was measured in 19 patients with inflammatory bowel diseases using gut mast cells from enzymatically dispersed endoscopic forceps biopsy specimens of macroscopically inflamed and normal tissue. Mast cells and corresponding basophils were challenged with anti-IgE, anti-IgG, subclass anti-IgG4, and formyl-methionyl-leucyl-phenylalanine (FMLP) and results were compared with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 16 publications
4
67
0
1
Order By: Relevance
“…Histamine is stored in mast cells and extracellularly released by stimulation [14]. It has been demonstrated that concentrations of TNF-␣, histamine, and IL-8 are increased in the affected intestinal mucosa of inflammatory bowel diseases [16][17][18][19][20]39], and symptoms correlate with the magnitude of neutrophil accumulation in the intestinal epithelium and mucosa [7]. In this study, we have revealed that stimulation of intestinal epithelial cells with TNF-␣ or hista-mine increases neutrophil adhesion to epithelial cells, and that stimulation of neutrophils with IL-8 or TNF-␣ up-regulates surface expression of CD11b/CD18 molecules and increases neutrophil adhesion to epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histamine is stored in mast cells and extracellularly released by stimulation [14]. It has been demonstrated that concentrations of TNF-␣, histamine, and IL-8 are increased in the affected intestinal mucosa of inflammatory bowel diseases [16][17][18][19][20]39], and symptoms correlate with the magnitude of neutrophil accumulation in the intestinal epithelium and mucosa [7]. In this study, we have revealed that stimulation of intestinal epithelial cells with TNF-␣ or hista-mine increases neutrophil adhesion to epithelial cells, and that stimulation of neutrophils with IL-8 or TNF-␣ up-regulates surface expression of CD11b/CD18 molecules and increases neutrophil adhesion to epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine content and its secretion have been found to be significantly increased particularly in affected mucosa of ulcerative colitis and Crohns disease compared with unaffected tissues [16,17]. Moreover, TNF-␣ concentrations are demonstrated to be markedly increased in the affected intestinal mucosa, serum, and feces of active inflammatory bowel diseases [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Mast cells in the lamina propria and submucosa have been implicated as contributors to local inflammation during IBD because of their ability to synthesize mediators such as histamine, prostaglandins, leukotrienes, cytokines, chemokines, and proteases. 15,35,36 The W sh mice were found to be more resistant to DSS-induced weight loss and mucosal damage in the cecum than C57BL/6 mice, a process that was confirmed to be mast cell-dependent by reconstitution studies. Mast cells have been shown by a number of groups to modify the epithelial barrier function within the intestine and, when activated, to increase intestinal permeability and fluid loss.…”
Section: Discussionmentioning
confidence: 81%
“…15,35,36 To date, no reported studies have examined the contribution of the mast cell during DSS colitis using mast cell-deficient Kit W-sh/W-sh (W sh ) mice. Mast cell-deficient mice, wild-type C57BL/6, and W sh mice reconstituted intravenously with 7.5 ϫ 10 6 C57BL/6 BMMCs were all treated with 3% DSS for 5 days, followed by 2 or 5 days of regular drinking water.…”
Section: Mast Cell-deficient W Sh Mice Are Less Susceptible Than Wildmentioning
confidence: 99%
See 1 more Smart Citation